Strategic airline operation considering the carbon constrained air transport industry. (July 2017) - Ko, Young Dae; Jang, Young Jae; Kim, Dae Young
Abstract: The EU emissions trading system (EU-ETS) is the EU's policy to combat climate change by reducing greenhouse gas emissions cost-effectively. CO2 emissions from aviation have been included in the EU-ETS since 2012, and all airlines operating in Europe are required to report and submit allowances against those emissions. The EU-ETS is only applied to flights that begin or end in EU territory, therefore one of the options non-EU based airlines use to deal with the EU-ETS requirements is aircraft reassignment or flight route adjustment. We investigate strategic airline operations that address the carbon constraints on the air transport industry. A mathematical model and algorithm are developed to derive efficient strategies for airline operations in terms of aircraft reassignment and route adjustment. The proposed mathematical model and heuristic algorithm are verified with a numerical example. The results of this study provide practitioners with insights when dealing with environmental restrictions on airlines. Highlights: Strategic airline operation are dealt against carbon constrained air transport market. Aircraft reassignment and flight route adjustment are considered as countermeasures. Nonlinear mathematical model is formulated and Genetic algorithm is proposed. Numerical example is generated by regarding EU-ETS for certain airline out of EU. Both an inefficient and an efficient aircrafts acts different ways with its features.